Protocolo de Observação do Desempenho de Crianças com Deficiência Física: Construção, Aplicação e Análise de Dados - Zafani, Mariana Dutra [UNESP]; Omote, Sadao [UNESP]; Baleotti, Luciana Ramos [UNESP] (FapUNIFESP (SciELO), 2015)
The article describes the procedures of construction, application and data analysis of an instrument of evaluation labeled Observation Protocol of Physically Disabled Children’s Performance in the Accomplishment of Painting and Pasting Activities. This protocol seeks to identify parent and teacherperception concerning two aspects of physically disabled children’s performance, i.e., the capacity or inability and independence or dependence with which they accomplish an activity they are familiar with in the school setting. Elevenpreschool and elementary school teachers and three researchers with experience in the area of Special Education participated in the study. A questionnaire was used to evaluate, according to the teachers’ perception, the suitability of the painting and pasting activities proposed to four to nine year old children. Another questionnaire was used to examine the opinion of the researchers about the adequacy of the proposed instrument for the intended aim. A series of procedures was accomplished to reach the final version of the instrument. Once finalized, the procedures for its application and data analysiswere systematized. The initial applications of the instrument have suggested that the instrument is fulfilling its main purpose, that is, the measurement of parents’ and teachers’ perception of physically disabled children’s performance in agiven activity that is often performed in the classroom. The results also suggest it be adapted regarding language and format for the population that will be using it.
Observation protocol of physically disabled children’s performance: Construction, application and data analysis
Keywords: Measurement instruments; Parents; Social perception; Special education; Teachers